Studying the effects of granisetron, ketamine, and pethidine on prevention of shivering induced by spinal anesthesia - Alaa El-Deen M Sayed (Wolters Kluwer Medknow Publications, 2018)
Background Spinal anesthesia avoids the hazards of airway management during general anesthesia. Shivering is a frequent risk factor in patients undergoing lower half operations under spinal anesthesia. Premedication with intravenous serotonin receptor antagonists such as granisetron has been used to overcome this problem. Ketamine increases arterial pressure and heart rate and may decrease core-to-peripheral redistribution of heat. Moreover, pethidine which is considered as a time-tested drug for control of shivering can be of value for shivering prophylaxis. Objective This study evaluates the efficacy of granisetron, ketamine, and pethidine on shivering in patients undergoing lower half operation under spinal anesthesia. Patients and methods A total of 60 patients were assigned to three equal groups: group G received 3 mg granisetron, group K received 25 mg ketamine, and group P received 25 mg pethidine 5 min before spinal anesthesia. The incidence of shivering episodes was recorded at baseline monitoring, intraoperatively, and postoperatively. Moreover, propagation and regression of motor and sensory block were assessed. Results Regarding mean arterial blood pressure, there was significant decrease in group P in comparison with groups G and K. Regarding decreased incidence of shivering, there was no significant difference between the study groups. Regarding incidence of nausea and vomiting, there was significant decrease incidence in group G compared with groups K and P. Moreover, there was significant difference regarding faster time to regression of sensory block in group G in comparison with groups K and P. Conclusion In patients undergoing lower half surgery under spinal anesthesia, prophylactic intravenous administration of 3 mg granisetron, 25 mg ketamine, or 25 mg pethidine 5 min before induction of spinal anesthesia significantly reduced the severity of shivering. Regression of sensory block was faster with granisetron than ketamine and pethidine. Moreover, prophylactic granisetron also reduces nausea and vomiting and the need of antiemetics.